Ніжинський грецький суд та магістрат у ХVІІ–ХІХ ст. - Пилипенко, О. (Сiверянський лiтопис, 2019)
Наукова стаття присвячена діяльності Ніжинського грецького суду та магістрату.
Вивчено основні напрямки діяльності магістрату ніжинських греків, його значення
для життя громади. Досліджено правову базу функціонування Ніжинського грецького
братства та його юридичний статус. Детально проаналізовано основні справи, які
розглядав та вирішував магістрат, визначено його компетенцію і співпрацю з іншими
магістратами Російської імперії. Окреслено подальші напрямки дослідження даної
теми. The scientific article is devoted to activity of the Nizhin Greek Court and Magistrate. The
main directions of activity of the Nizhin Greeks Magistrate, it value for life of brotherhood are
studied. The legal status and law base of function of Nizhin Greek merchants brotherhood in
the territory of Ukraine are investigated. Many cases was anylysed by state were determine,
his competence and cooperation with other magistrate of the Russian Empire. Further of
researching of this topic are outlined.
The Greek Nizhin court played an important role in life of the Greek migrants. Exactly
the newly arrived Greeks trusted consideration of commercial and civil businesses him. He
got the name of «mediation court» yet. Because judge mediator that was appointed from a
number the most worthy, authoritative and experience Greek merchants. In course of time in
city Nizhin there was own the Greek city magistrate (council) carried out the activity next
to the Nizhin municipal city council. But unlike the last, he decided business exceptionally of
citizen foreigners. The Nezhin city Greek magistrate became an original center that joined
Greeks and other foreign migrants in Ukraine.
Many business that was examined a city council were saved in the archive documents.
Mainly these were criminal, civil, commercial, administrative cases. It was not accepted to
appeal the decitions of Greek magistrate and cases of appeals were single. Activity of members
of the Nizhin Greek magistrate used large respect and honour of fellow-citizens. Nizhin Greek
magistrate was activity until 1868 year.